Shorter versus longer corticosteroid duration and recurrent immune checkpoint inhibitor-associated AKI - Gupta, Shruti; Garcia-Carro, Clara; Prosek, Jason M.; Glezerman, Ilya; Herrmann, Sandra M.; Garcia, Pablo; Abudayyeh, Ala; Lumlertgul, Nuttha; Malik, A. Bilal; Loew, Sebastian; Beckerman, Pazit; Renaghan, Amanda D.; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Corticosteroids are the mainstay of treatment for immune checkpoint inhibitor-associated acute kidney injury (ICPi-AKI), but the optimal duration of therapy has not been established. Prolonged use of corticosteroids can cause numerous adverse effects and may decrease progression-free survival among patients treated with ICPis. We sought to determine whether a shorter duration of corticosteroids was equally efficacious and safe as compared with a longer duration.
Gesehen am 13.01.2023